2017
DOI: 10.1002/macp.201700015
|View full text |Cite
|
Sign up to set email alerts
|

Living Anionic Polymerization of 1‐Adamantyl 4‐vinylphenyl ketone

Abstract: The anionic polymerization of 1-adamantyl 4-vinylphenyl ketone (1), a styrene derivative carrying an electrophilic carbonyl group, is carried out in tetrahydrofuran (THF). Although no polymerization of 1 occurs with sec-BuLi at −78 °C for 48 h, a polymeric product of 1 is obtained with diphenylmethyllithium in 10% yield under similar conditions. The resulting poly(1) has a very broad molar-mass dispersity (Đ M = M w /M n = 1.72) and a molecular weight higher than the calculated value based on the molar ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…The incorporation of the bulky and rigid adamantyl framework to poly(α‐methylstyrene) as a pendant group induces the high T g value of poly( AdαMS ) at 274 °C, which is almost 110 °C higher than the parent poly(α‐methylstyrene). Thus, it is demonstrated that AdαMS is a new class of adamantyl‐substituted vinyl monomer giving the anionic living polymer, similar to the previous examples of AdS , Ad2S , N ‐(1‐adamantyl)‐ N ‐4‐vinylbenzylideneamine, and 1‐adamantyl 4‐vinylphenyl ketone …”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The incorporation of the bulky and rigid adamantyl framework to poly(α‐methylstyrene) as a pendant group induces the high T g value of poly( AdαMS ) at 274 °C, which is almost 110 °C higher than the parent poly(α‐methylstyrene). Thus, it is demonstrated that AdαMS is a new class of adamantyl‐substituted vinyl monomer giving the anionic living polymer, similar to the previous examples of AdS , Ad2S , N ‐(1‐adamantyl)‐ N ‐4‐vinylbenzylideneamine, and 1‐adamantyl 4‐vinylphenyl ketone …”
Section: Resultssupporting
confidence: 74%
“…Recently, the living anionic polymerizations of styrenes carrying reactive moieties, N ‐(1‐adamantyl)‐ N ‐4‐vinylbenzylideneamine, and 1‐adamantyl 4‐vinylphenyl ketone are also achieved. The rigid and bulky adamantyl substituents effectively hindered any serious side reactions of the nucleophilic initiators and the propagating carbanion with the electrophilic CO and CHN groups and realized the living anionic polymerizations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations